Blood pressure control and glaucoma risk in postmenopausal women: an analysis from the Women's Health Initiative. Issue 5 (14th May 2022) - Haring, Bernhard; Hovey, Kathleen; LaMonte, Mike; Andrews, Chris; Saquib, Nazmus; Manson, JoAnn E.; Shimbo, Daichi; Ritch, Robert; De Moraes, Carlos Gustavo; Wassertheil-Smoller, Sylvia
Abstract: Objective: Individuals with elevated systolic blood pressure (BP) or low diastolic BP, whether or not on antihypertensive treatment, may be at higher risk for developing glaucoma. We aimed to investigate BP levels in relation to glaucoma risk in a large cohort of postmenopausal women. Methods: Prospective follow-up of 101, 447 postmenopausal women without prior history of glaucoma enrolled in the Women's Health Initiative Study. BP was measured in-clinic at baseline and after 3 years using standardized procedures. Antihypertensive medication use was determined by drug inventory at baseline and year 3. Women self-reported incident newly diagnosed glaucoma annually. Hazard ratios (HRs) and 95% confidence intervals were estimated using Cox proportional hazards analyses adjusting for demographic, medical history, and lifestyle covariates. Results: During a mean follow-up of 4.7 years, we documented 7, 514 glaucoma cases. Among women not on antihypertensive treatment, those with systolic BP ≥ 140 mm Hg or diastolic BP ≥80 mm Hg were not at higher risk of developing glaucoma (HR 0.97, 95% confidence intervals 0.88-1.08 and HR 1.00 [0.93-1.08], respectively), compared with women with a systolic BP < 120 mm Hg or a diastolic BP 60 to <80 mm Hg. Among women on antihypertensive treatment, neither systolic BP ≥ 140 mm Hg nor diastolic BP ≥80 mm Hg was associated with an increased glaucoma risk (HR 0.89 [0.79-1.00] and HR 0.97 [0.90-1.05], respectively). A diastolic BP <60 mm Hg was not associated with a higher risk compared with a diastolic BP 60 to <80 mm Hg. Conclusions: BP control is not associated with an increased or decreased glaucoma risk in postmenopausal women.